Expression of LRIG1 is Associated With Good Prognosis for Human Non-small Cell Lung Cancer. Issue 47 (November 2015) - An, Yuzhi; Zhao, Zibo; Ou, Pengju; Wang, Guangchuan
Abstract : Abstract: Somatic mutations, which are associated with a certain rate of response to targeted therapies, are ubiquitously found in human non-small cell lung cancer (NSCLC). However, it is largely unknown which group of patients may benefit from the respective treatments targeting different somatic mutations. Therefore, more effective prognostic and predictive markers are desperately needed for the treatment of NSCLC harboring different somatic mutations. The leucine-rich repeats and immunoglobulin-like domains (LRIG)-1 is a tumor suppressor gene that belongs to the LRIG family. LRIG1 expression has prognostic significance in various human cancers. In this study, we first used the quantitative polymerase chain reaction (qPCR) and immunohistochemical analysis of 36 and 182 NSCLC patient tissues to analyze the LRIG1 expression respectively. To investigate the prognostic value of LRIG1 in NSCLC, we examined the correlation between clinical features and overall survival (OS) with Cox proportional hazard regression. We also compared the sensitivity and specificity of LRIG1 in NSCLC prognosis by logistic regression to further evaluate the prognostic efficiency of LRIG1 in NSCLC. We found that the LRIG1 expression was associated with pathological type, differentiation status, and stage of NSCLC. The result showed that LRIG1 was an independent prognostic factor for OS of NSCLC patients. LRIG1 in combination with other clinicopathological risk factors was a stronger prognostic model than clinicopathological risk factors alone. Thus, the LRIG1 expression potentially offered a significant clinical value in directing personal treatment for NSCLC patients.